2013
DOI: 10.1097/dad.0b013e31827eaf0b
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine-Associated Retiform Purpura

Abstract: Cocaine-associated retiform purpura is a recently described entity characterized by striking hemorrhagic necrosis involving areas of skin associated with administration of cocaine. Levamisole, an adulterant in cocaine, has been suggested as the main culprit pathogenetically. Four cases of cocaine-associated retiform purpura were encountered in the dermatopathology practice of C. M. Magro. The light microscopic findings were correlated with immunohistochemical and immunofluorescence studies. All 4 cases showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…It has been reported that sublytic C5b-9 is able to induce cell apoptosis in many types of cells; 20, 44, 45 however, sublytic C5b-9 can protect oligodendrocytes from apoptosis and lead to survival, 46 suggesting that the different response to C5b-9 in these cells may be because of different cell types and different biochemical reactions upon sublytic C5b-9 attack. It is worth mentioning that sublytic C5b-9 was also found to be able to induce GMC proliferation at 36 and 54 h after sublytic C5b-9 stimulation in our previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that sublytic C5b-9 is able to induce cell apoptosis in many types of cells; 20, 44, 45 however, sublytic C5b-9 can protect oligodendrocytes from apoptosis and lead to survival, 46 suggesting that the different response to C5b-9 in these cells may be because of different cell types and different biochemical reactions upon sublytic C5b-9 attack. It is worth mentioning that sublytic C5b-9 was also found to be able to induce GMC proliferation at 36 and 54 h after sublytic C5b-9 stimulation in our previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Other antibodies that may be observed are antiphospholipid, antinuclear, and anti-DNA antibodies . Finally, cocaine metabolites have been demonstrated to enhance the synthesis and deposition of complement C5b-9, leading to thrombotic microangiopathy phenomena, even without the presence of vasculitis …”
Section: Discussionmentioning
confidence: 99%
“…leading to thrombotic microangiopathy phenomena, even without the presence of vasculitis. 6 Accordingly, the classic differential diagnoses of cocaine-related skin diseases include various neutrophilic disorders, such as cocaine-induced midline destructive lesions, ANCA-associated vasculitis-retiform purpura/ cocaine-levamisole-associated autoimmune syndrome (CLAAS), pyoderma gangrenosum, pyostomatitis vegetans and neutrophilic dermatosis of the dorsal hands (eFigure 1 in Supplement 1). 2,4,7,8 For all of them, neutrophils, vasculitis, and intravascular thrombotic phenomena in the results of biopsy are diagnostic hallmarks.…”
Section: Meaningmentioning
confidence: 99%
“…Tanhehco et al showed that cocaine increased the gene expression of several complement components and the protein expression of the terminal complement complex C5b-9 in the rabbit heart [ 2 ]. Magro et al reported extensive vascular C5b-9 deposition in cocaine-induced retiform purpura that is characterized by skin necrosis secondary to cutaneous TMA [ 3 ]. Durán et al reported a 28-year-old man with complement factor H deficiency who developed TMA (aHUS) triggered by cocaine use [ 11 ].…”
Section: Discussionmentioning
confidence: 99%